Impact of antiretroviral therapy on fertility desires among HIV-infected persons in rural Uganda - Alibhai Arif; Jhangri Gian S; Heys Jennifer; Kipp Walter; Rubaale Tom (BMC, 2011)
Abstract Background Little is known about the fertility desires of HIV infected individuals on highly active antiretroviral therapy (HAART). In order to contribute more knowledge to this topic we conducted a study to determine if HIV-infected persons on HAART have different fertility desires compared to persons not on HAART, and if the knowledge about HIV transmission from mother-to-child is different in the two groups. Methods The study was a cross-sectional survey comparing two groups of HIV-positive participants: those who were on HAART and those who were not. Semi-structured interviews were conducted with 199 HIV patients living in a rural area of western Uganda. The desire for future children was measured by the question in the questionnaire "Do you want more children in future." The respondents' HAART status was derived from the interviews and verified using health records. Descriptive, bivariate and multivariate methods were used to analyze the relationship between HAART treatment status and the desire for future children. Results Results from the multivariate logistic regression model indicated an adjusted odds ratio (OR) of 1.08 (95% CI 0.40-2.90) for those on HAART wanting more children (crude OR 1.86, 95% CI 0.82-4.21). Statistically significant predictors for desiring more children were younger age, having a higher number of living children and male sex. Knowledge of the risks for mother-to-child-transmission of HIV was similar in both groups. Conclusions The conclusions from this study are that the HAART treatment status of HIV patients did not influence the desire for children. The non-significant association between the desire for more children and the HAART treatment status could be caused by a lack of knowledge in HIV-infected persons/couples about the positive impact of HAART in reducing HIV transmission from mother-to-child. We recommend that the health care system ensures proper training of staff and appropriate communication to those living with HIV as well as to the general community.